Status of LET assessment with active and passive detectors in ion beams - Christensen, Jeppe Brage; Muñoz, Iván Domingo; Bilski, Pawel; Conte, Valeria; Olko, Pawel; Bossin, Lily; Vestergaard, Anne; Agosteo, Stefano; Rosenfeld, Anatoly; Tran, Linh; Knežević, Željka; Majer, Marija; et al. (Radiation measurements, 2024)
This review explores current experimental methods for determining the radiation quality in ion beams. In this context, radiation quality is commonly evaluated using the averaged linear energy transfer (LET), a metric employed to assess the response of both biological and physical systems. Dose and averaged LET can be experimentally determined with passive detectors through various techniques that have seen recent improvements. Another metric related to the LET is the mean lineal energy, which is measurable using microdosimetric detectors. This review focuses on the available possibilities for evaluating the radiation quality using three microdosimeters (mini-TEPC, Silicon Telescope, and SOI Microplus), three passive luminescence detectors (based on optical, thermo-, and radiophoto-luminescence), three track-based detectors (track-etched detector, Timepix, fluorescent nuclear track detector), and a chemical detector based on alanine. A comparison of detector properties is provided along with an overview of the underlying mechanisms enabling LET assessment or measurements of the mean lineal energy with each detector type. Finally, this review summarizes the current possibilities of LET determination with respect to the needs for quality assurance in particle therapy. Areas for future research and development are suggested.
Online verfügbar: 24. Juli 2024, Artikelversion: 1. August 2024
Gesehen am 29.09.2025